SDGs-based adaptive curriculum model to improve education quality in the digital age - Eva Puspitasari (Inovasi Kurikulum)
The rapid advancement of technology and global sustainability issues demand innovations in educational curricula aligned with the Sustainable Development Goals (SDGs), specifically SDG 4 on quality education. This article examines the development of an adaptive curriculum model based on SDGs designed to enhance education quality in the digital era. Emphasizing 21st-century skills, such as critical thinking, creativity, collaboration, and digital literacy, this model prepares students to respond more to global challenges. The research employs a descriptive qualitative approach through a literature review, analyzing sources related to SDG implementation in education. Findings indicate that integrating technology into the curriculum enables more inclusive and interactive learning, reaching students in remote areas. The Project-Based Learning (PjBL) and Problem-Based Learning (PBL) approaches adopted in this curriculum have proven effective in enhancing students' skills in solving real-world problems. In conclusion, this SDG-based adaptive curriculum model has the potential to create a generation that is not only academically competent but also socially aware and sustainability-oriented, providing essential skills for navigating dynamic global changes.